PENYELESAIAN SENGKETA JALUR MEDIASI SEBAGAI PERWUJUDAN KEMBALINYA HUKUM BERBASIS KEARIFAN LOKAL - Randy Atma (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
Indonesia has been agreed in the constitution as a state based on law (Rechstaat), which has a Civil Law system, but in the history of the development of society before knowing writing and even the existence of written law, people in the archipelago have had their own way to find solutions to social problems carried out with customary values ​​and traditions of morality-based beliefs which are currently known as customary law with the mechanism of Deliberation and Consensus. With the promulgation of the Arbitration Law, the existence of dispute resolution outside the court is further strengthened, of course this opens space for people who actually prefer to carry out a mediation process outside the court route because it is considered more of a solution than solving legal problems through the courts.